Implementasi Bentuk Wakul Dengan Pendekatan Analogi Pada Perancangan Fasilitas Pertunjukan Tari Boran - Syafi'uddin, Muhammad Rizqi; Soemarwanto, Dadoes (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2024)
Various traditional arts are truly national cultural assets, one of which is Lamongan Regency, one of which is Boranan culture in Lamongan Regency. In 2023, the Boran dance won a MURI record. The dance performance was attended by 1,569 students and 4,540 portions of Boran rice were based on the philosophy of the anniversary year. Lamongan, namely in 1,569 AD, which is currently 454 years old. Apart from that, the Boran dance was also able to win awards at the provincial and national levels. The art of boran dance cannot be separated from the culinary boran rice, culinary rice boran is a typical food of Lamongan Regency which has been around for a long time in Lamongan Regency. Then what is the solution so that Boranan culture becomes more widely known and can become a tourist destination in Lamongan district by creating or designing facilities that are able to facilitate and present Boranan culture. This research uses descriptive methodology which is carried out by collecting data. Design of Boranan cultural facilities, using the concept of local wisdom with a direct analogy approach to elevate local culture, especially Boranan culture, in an architectural form that is able to represent Boranan culture and is able to make Boranan culture a tourist destination in Lamongan district.